QUALITY IMPROVEMENT The Second Conversation project: Improving training in end of life care communication among junior doctors. Issue 2 (2019) - Mathew, Rammya; Weil, Anna; Sleeman, Katherine E; Bristowe, Katherine; Shukla, Praphull; Schiff, Rebekah; Flanders, Lucy; Leonard, Pauline; Minton, Ollie; Wakefield, Dominique; John, Kimberley St; Carey, Irene
No abstract available